Exploring Local Wisdom: Case Study of Rumah Bolon in North Sumatra - Nabila, Putri; Harnum, Sintia (Holistic Science, 2024)
This article reviews a traditional Toba Batak house, known as a bolon house. The bolon house is an important symbol for the Toba Batak community in North Sumatra, Indonesia. In this paper, we describe the architectural characteristics of the bolon house, including building materials, structure, and its functions in the daily life of the Toba Batak community. This article also explores how the bolon house serves not only as a place to live but also as a place for social gatherings, religious ceremonies, and family celebrations cultural analysis, we explore how the bolon house serves not only as a place to live but also a place for social gatherings, religious ceremonies, and family celebrations. The research aims to deepen the understanding of Indonesian traditional beliefs and the importance of family life as a means of preserving the identity and culture of the Toba Batak people. Family life as a means of preserving the identity and culture of the Toba Batak community. Thus, this article contributes to the literature on vernacular architecture and religious rituals in Indonesia and encourages readers to recognize and understand the distinctive characteristics of local customs.